The Study of Adolescent Resilience (SOAR): a research protocol - Karen Tannenbaum; Karen Tannenbaum; Hope Seib McMaster (Frontiers Media S.A., 2024)
BackgroundAdolescence is a particularly sensitive period of development for military-connected youth, given the socioemotional and physical changes that occur against the backdrop of the military career of their parent(s). Military-connected adolescents face unique stressors relative to their civilian counterparts, such as military relocations, parental absence due to deployments and trainings, and parental military-related physical and mental injury. These stressors may change family dynamics and disrupt social support networks, which can have lasting implications for adolescent health and well-being. At present, very little is known about how the current generation of military-connected adolescents are faring regarding their psychological and physical health, academic achievement, and educational or career aspirations. As part of the Biden-Harris Administration's commitment to military families, the U.S. Department of Defense pledged to address these major knowledge gaps by supporting the Study of Adolescent Resilience (SOAR). SOAR's longitudinal design provides a powerful tool for evaluating the effects of military family life on adolescent well-being into early adulthood.Methods and designSOAR is embedded within the larger Millennium Cohort Study, the first U.S. population-based prospective study to investigate long-term health effects of military service among active duty service members. Nearly 40,000 Millennium Cohort participants with adolescent children were invited to complete a web-based self-report survey that included items across interpersonal, socioenvironmental, and health domains, among others. Military parents provided referral information for their adolescent child and another primary parental figure, when available, to be invited to SOAR. This approach allowed survey data to be linked between these three family members (service member, spouse, and adolescent) to promote a comprehensive, family systems-based understanding of military-connected adolescent experiences and determinants of health, risk, and resilience.DiscussionResearch findings will shed light on the enduring impact of military life on adolescents and the nature of associations between military-specific experiences and psychosocial health and well-being. Further, this research will assess modifiable risk and protective factors that may elucidate differences in military-connected adolescent psychosocial development and physical health, academic achievement, and educational and military career aspirations over time.ConclusionsFindings gleaned from this research will be used to inform existing policy and programs designed to promote adolescent resilience.